The effects of stimulus distribution form during trace conditioning - Bonardi, Charlotte; Jennings, Dómhnall J. (Taylor & Francis, 2017)
Three experiments examined the effect of the distribution form of the trace interval on trace conditioning. In Experiments 1 and 2 two groups of rats were conditioned to a fixed duration CS in a trace interval procedure; rats in Group Fix received a fixed duration trace interval whereas for rats in Group Var the trace interval was of variable duration. Responding during the CS was higher in Group Var than in Group Fix, whereas during the trace interval this difference in responding reversed – Group Fix showed higher response rates than Group Var. Experiment 3 examined whether the greater response rate observed during the CS in Group Var was due to a performance effect, or the acquisition of greater associative strength by the CS. Following trace conditioning, the rats from Experiment 1 underwent a second phase of delay conditioning with the same CS; a 5-s auditory stimulus was presented in compound with the last 5s of the 15-s CS, and the US was delivered at the offset of the CSs. On test with the auditory stimulus alone, subjects in Group Var showed lower response rates during the auditory stimulus than subjects in Group Fix. We interpreted these findings as evidence that the superior responding in Group Var during the CS was a result of it acquiring greater associative strength than in Group Fix.